If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4a + -1) = 7(2a + -7) Reorder the terms: 3(-1 + 4a) = 7(2a + -7) (-1 * 3 + 4a * 3) = 7(2a + -7) (-3 + 12a) = 7(2a + -7) Reorder the terms: -3 + 12a = 7(-7 + 2a) -3 + 12a = (-7 * 7 + 2a * 7) -3 + 12a = (-49 + 14a) Solving -3 + 12a = -49 + 14a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-14a' to each side of the equation. -3 + 12a + -14a = -49 + 14a + -14a Combine like terms: 12a + -14a = -2a -3 + -2a = -49 + 14a + -14a Combine like terms: 14a + -14a = 0 -3 + -2a = -49 + 0 -3 + -2a = -49 Add '3' to each side of the equation. -3 + 3 + -2a = -49 + 3 Combine like terms: -3 + 3 = 0 0 + -2a = -49 + 3 -2a = -49 + 3 Combine like terms: -49 + 3 = -46 -2a = -46 Divide each side by '-2'. a = 23 Simplifying a = 23
| -8(x+1)=4(x-1) | | -10(s+3)=-43 | | -(c+6)=1 | | 2(x-4)+3(2-x)+2x+2= | | 7(2l+8)=122 | | 2x-45=90 | | X^5=230 | | x^3-27x^2+12=0 | | 0.43=0.0814ln(x)+0.3357 | | 3sin(x)-2cos(x)=0 | | a-2a-3=0 | | -3y=5t | | x+10-16=1 | | 3*b-b*(-3)+3*(-b)= | | 3X-21=4X-36 | | Ln*(x-4)+ln*(x-7)=ln*18 | | 3xb-bx(-3)+3x(-b)= | | 1/3k-1=4/6 | | In*(x-6)+In*(x-4)=In*15 | | 6x-9-4x=13 | | (4y+7)(4-y)=0 | | q(z)=pz+b | | ln*(x-5)+ln*(x-8)=ln*28 | | x-1/5=3-(x-9)/2 | | (150-80/1-x)2x=0 | | 40-(5)x=8+x | | (5-3x)2x=0 | | (4g-2)*(4g-2)=4 | | 3(2m-8)-4m=20 | | 2sinx=5+cosx | | 4.5=4t^2 | | 7x^2+7x=9 |